Applicazioni di Realtà Aumentata in ambiente GIS - Conti, Giuseppe; De Amicis, Raffaele; Piffer, Stefano; Simoes, Bruno (GEOmedia, 2008)
Augmented Reality applications in the GIS environment Technological development, reduced hardware cost and wide use of 3D GIS applications are paving the way to the adoption of advanced visualisation technologies. Examples of such technologies are Augmented Reality (AR), with particular application in the geospatial domain. AR allows real-time synchronisation of computer-generated information onto the images of the real scene facilitating applications designed for design, maintenance and surveying on site. This paper presents an AR-GIS application specifically developed for the context of environmental management, detailing both its hardware and software architecture. The results demonstrate that the level of maturity reached in AR render it highly applicable in the geospatial domain.